2021
DOI: 10.1186/s12909-021-02512-2
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition from the kitchen: culinary medicine impacts students’ counseling confidence

Abstract: Background Although a poor diet is the number one risk factor for early death in the United States and globally, physicians receive little to no training in dietary interventions and lack confidence counseling patients about lifestyle modifications. Innovative, interprofessional strategies to address these gaps include the emergence of culinary medicine, a hands-on approach to teaching the role of food in health outcomes. We sought to assess the impact of a culinary medicine elective on counsel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(65 citation statements)
references
References 55 publications
1
53
1
Order By: Relevance
“…The number of participants ranged from four [ 38 ] to 4215 [ 46 ]. Twenty studies involved medical students only [ 34 , 35 , 38 42 , 44 46 , 48 , 49 , 51 , 52 , 54 – 59 ], nine of which evaluated a single year cohort of students rather than a mixed cohort between years one through four of their medical program [ 38 , 40 , 42 , 52 , 55 – 59 ]. Two studies involved medical students and medical registrars [ 45 , 47 ], and two also included nutrition students [ 43 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The number of participants ranged from four [ 38 ] to 4215 [ 46 ]. Twenty studies involved medical students only [ 34 , 35 , 38 42 , 44 46 , 48 , 49 , 51 , 52 , 54 – 59 ], nine of which evaluated a single year cohort of students rather than a mixed cohort between years one through four of their medical program [ 38 , 40 , 42 , 52 , 55 – 59 ]. Two studies involved medical students and medical registrars [ 45 , 47 ], and two also included nutrition students [ 43 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies reported the study population demographics, with participants from varying ethnicities and nutritional backgrounds [ 34 , 44 46 , 48 52 , 56 – 58 ]. The recruitment process in the studies typically involved an open elective application ( n = 6) [ 42 , 49 , 50 , 55 , 56 , 59 ], or voluntary enrolment into the course ( n = 8) [ 38 , 39 , 43 , 44 , 48 , 51 , 52 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, many new innovations have been developed to teach and integrate nutrition education in medical and dental curricula in recent years [45]. For example, a new interactive teaching and learning platform, "Health Meets Food", features specifically designed online interactive course modules, continuing education credits and online videos to complement and enhance applied nutrition education in clinical training programs, including medicine and dentistry [46,47]. It has been demonstrated that these interactive courses and education modules may improve and achieve dietary sodium recommendations among cardiovascular patients, as well as reducing heart-failure-associated readmissions and improving HbA1c, blood pressure and cholesterol levels for patients with adult onset or Type II diabetes [48][49][50].…”
Section: Discussionmentioning
confidence: 99%